2022
DOI: 10.3390/nu14051018
|View full text |Cite
|
Sign up to set email alerts
|

Betel Nut Chewing Increases the Risk of Metabolic Syndrome and Its Components in a Large Taiwanese Population Follow-Up Study Category: Original Investigation

Abstract: Betel nut chewing is a popular habit in Taiwan, and it is associated with adverse metabolic effects. The aim of this study was to investigate correlations between betel nut chewing with metabolic syndrome (MetS) and its components in a longitudinal study using data from the Taiwan Biobank. A total of 121,423 participants were included in the baseline study, and 27,002 received follow-up examinations after a median of 4 years. The association between betel nut chewing and MetS was analyzed using multiple logist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
(64 reference statements)
0
4
0
Order By: Relevance
“…Similarly, betel nut chewing has been associated with low HDL-C levels, and this effect may be more prominent than its influence on other MetS features, e.g. elevated TG and BP ( 7 ). For alcohol use, the association with reduced HDL-C was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, betel nut chewing has been associated with low HDL-C levels, and this effect may be more prominent than its influence on other MetS features, e.g. elevated TG and BP ( 7 ). For alcohol use, the association with reduced HDL-C was inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of MetS has been on the rise globally, and it has become a significant public health concern (4,5). Numerous studies have investigated the association between various lifestyle factors, such as alcohol consumption, smoking, and betel nut chewing, and the development of MetS (6)(7)(8)(9)(10). However, the synergistic effect of these unhealthy lifestyle behaviors on the incidence of MetS, particularly among physically active young adults, has not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chewing betel nuts, also known as betel quid or areca nuts, is widespread throughout South and Southeast Asia, East Africa, and the Western Pacific and plays an important role in the sociocultural identity [27]. Moreover, the consumption of betel quid is associated with MetS, diabetes, hypertension, obesity, cardiovascular disease [28][29][30], and cancer of the oral cavity, pharynx, and esophagus [31]. A cross-sectional research of 667 male Taiwanese participants found a link between betel nut consumption and CKD, with an adjusted odds ratio of 2.572 (95%CI 1.917, 3.451) [32], which is consistent with our finding.…”
Section: Discussionmentioning
confidence: 99%